Tevatron searches for Higgs and supersymmetry - Claes, Daniel R. (Array, 2008)
Summary: Results are presented of searches for Standard Model and MSSM Higgs, as well as supersymmetric particles. A broad variety of signatures were explored by the CDF and DØ experiments, using approximately 2 fb-1 of reconstructed p[`p] data from collisions at 1.96 TeV at Fermilab's Tevatron. No significant deviation from background sources has been observed in any of the searches, and new limits have been set on the production cross sections